Orbital Ectopic Lymphoid Follicles with Germinal Centers in Aquaporin-4-IgG-Positive Neuromyelitis Optica Spectrum Disorders - Chan, Koon Ho; Lee, Raymand; Lau, Kui Kai; Loong, Florence (Frontiers in Immunology, 2018)
Neuromyelitis optica spectrum disorders (NMOSDs) are important autoimmune central nervous system (CNS) astrocytopathy causing acute myelitis, optic neuritis and encephalitis associated with significant morbidities and mortality. It is important to diagnose NMOSDs early as they are treatable. The majority of NMOSDs patients are seropositive for aquaporin-4 IgG (AQP4-IgG) autoantibodies which target CNS aquaporin-4 (AQP4) expressed abundantly in astrocytic foot processes. We report the novel observation of orbital masses containing ectopic lymphoid follicles with germinal centres in two patients with AQP4-IgG positive NMOSD. Both patients had severe extensive myelitis with symptomatic or asymptomatic optic neuritis, with the ectopic lymphoid structures detected on initial presentation. Histolopathological studies confirmed that the orbital masses contained reactive lymphoid follicles with germinal centres containing B cells and plasma cells. Our observations support that AQP4-IgG positive NMOSDs patients have underlying AQP4 autoimmunity, and suggest that optic neuritis (symptomatic or asymptomatic) may trigger formation of orbital ectopic germinal centres contributing to development of high-affinity AQP4-specific memory B cells and plasma cells which produce highly pathogenic AQP4-IgG.